Fetal alcohol syndrome: a prospective national surveillance study. Issue 9 (17th August 2007) - Elliott, E J; Payne, J; Morris, A; Haan, E; Bower, C
Abstract : Objective: To describe the epidemiology of cases of fetal alcohol syndrome (FAS) seen by Australian paediatricians. Methods: Active, national case-finding using the Australian Paediatric Surveillance Unit (APSU). Monthly reporting of incident cases aged <15 years by paediatricians between January 2001 and December 2004. Results: Over 1150 paediatricians submitted reports each month to the APSU. Of 169 reported cases, 92 fulfilled the study criteria for FAS. There was a significant increase in the number of children reported each year from 2001 to 2004. Of 92 children, 53.3% were male, 35.7% were preterm (<37 weeks' gestation) and 64.6% were of low birth weight (<2.5 kg). Most (94.4%) had high risk exposure to alcohol in utero and 78.3% were exposed to one or more additional drugs. The median age at diagnosis was 3.3 years (range: newborn to 11.9 years): 6.5% were diagnosed at birth and 63% by 5 years of age. Of the 92 cases, 56% had growth deficiency, 53.2% had microcephaly, 85.9% had evidence of central nervous system dysfunction, 24% had additional birth defects, 5.4% had sensorineural deafness and 4.3% had visual impairment. Of children with FAS, 65% were Indigenous, 51% had a sibling with FAS, and only 40.2% lived with a biological parent. Conclusion: Our data are the only prospective national data available on FAS throughout the world. These findings highlight the severity, complexity and impact of FAS, the need for effective strategies for prevention, and the necessity for education to facilitate earlier diagnosis, referral and reporting of cases.